Student Factors and Parental Involvement on Academic Performance of Senior Secondary School Students Qualifying Examination in Osun State Secondary Schools - Oluwasola Damilola Owoeye; Bamidele Abiodun Faleye; Kasali Jimoh (MO.RI Publishing, 2022)
The study examined Osun State senior secondary school students’ performance identified factors that affect senior secondary school students’ performance, and factors contributing to students’ performance. The study adopted the descriptive survey research design. The population of the study comprised all 243 public senior secondary schools in Osun State. A sample of 600 Senior Secondary Two (SS II) students was selected using a multistage sampling procedure. The instruments used for data collection were questionnaire and pro-forma. Three forms of the questionnaire were used; they are Questionnaire on Student Factors and Parental Involvement on Academic Performance designed for students in secondary schools (QSFPIAPSSS), Questionnaire on Academic Performance designed for secondary school teachers (QAPSST), Questionnaire on Academic Performance designed for secondary school administrators (QAPSSA). The pro-forma on students’ academic performance in 2017 qualifying examination was used to collect academic performance record. The data collected were analyzed using frequency, counts and multiple regression. The results showed that 12.2% of the students sampled had low-level academic performance, while 10.2% of them had high-level academic performance. Results also showed that study habit (18.6%), self-efficacy (16.8%), parental care (47.6%) and teachers’ influence (36.3%) significantly affect students’ academic performance. The study concluded that students’ habit, self-efficacy, parental care and teachers’ influence were the strongest factors that contribute significantly to students’ academic performance in qualifying examination in Osun State Secondary Schools.